2004
DOI: 10.1175/bams-85-10-1565
|View full text |Cite
|
Sign up to set email alerts
|

THE BALTEX BRIDGE CAMPAIGN: An Integrated Approach for a Better Understanding of Clouds

Abstract: Sensor synergy and close cooperation between experimentalists and modelers is required to gain more insight into complex cloud structures and processes. On a global scale, clouds have a strong cooling effect on our climate: more solar radiation is reflected back to space than thermal surface radiation is trapped in the atmosphere. However, because radiation reacts on the instantaneous cloudy atmosphere and not on some climatological mean, the physical processes leading to the overall radiative effect strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…For this intercomparison, individual model transferability experiments will be defined as simulating cloud systems of different origins, structures, and evolution within a single domain by a single model. From a comparison of the results of NWP and RCMs with measurements taken during an enhanced observational period of the BALTEX BRIDGE experiment, Crewell et al (2004) observed that there are large discrepancies among the liquid water climatologies of models, and that a clear improvement in the simulation of clouds was achieved when 40 or more levels were used to resolve the fine structure of clouds. Simulations with regional models, some with enhanced vertical resolution, will be compared against intensive observations made during the Northern Hemisphere summer.…”
Section: Futu Re De Ve Lopm E Ntsmentioning
confidence: 99%
“…For this intercomparison, individual model transferability experiments will be defined as simulating cloud systems of different origins, structures, and evolution within a single domain by a single model. From a comparison of the results of NWP and RCMs with measurements taken during an enhanced observational period of the BALTEX BRIDGE experiment, Crewell et al (2004) observed that there are large discrepancies among the liquid water climatologies of models, and that a clear improvement in the simulation of clouds was achieved when 40 or more levels were used to resolve the fine structure of clouds. Simulations with regional models, some with enhanced vertical resolution, will be compared against intensive observations made during the Northern Hemisphere summer.…”
Section: Futu Re De Ve Lopm E Ntsmentioning
confidence: 99%
“…There has been enormous progress in the development and refinement of ground-based remote sensing instruments for Published by Copernicus Publications on behalf of the European Geosciences Union. the determination of humidity, wind, cloud parameters and rain rate in recent years (e.g., Bösenberg and Linné, 2002;Haeffelin et al, 2005;Peters et al, 2002;Intrieri et al, 2002), and also the retrieval algorithms for characterising clouds have been much improved in recent years, not least because of international projects like BALTEX BRIDGE with its subprogramm CLIWA-NET and CLOUDNET (http: //www.cloud-net.org), and the German 4D CLOUDS project (e.g., Crewell et al, 2004;Löhnert et al, 2004). In particular the CLOUDNET project has promoted the retrievals of cloud liquid water and cloud ice water content (e.g., Tinel et al, 2005;Liu and Illingworth, 2000;Hogan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Because microwave radiometry is the most accurate way to measure liquid water path, more than 10 different microwave radiometers from European universities and research organizations operated successfully during three enhanced observation phases-all part of BRIDGE, the major field experiment of BALTEX. Most importantly, the BALTEX BRIDGE Campaign (BBC; Crewell et al 2004) included multiple aircraft observations and a microwave intercomparison campaign that served as a baseline to develop an operational microwave radiometer for LWP and thermodynamic profiles (HATPRO; Rose et al 2005). Methodologies focusing on the evaluation of model-predicted cloud parameters with CLIWA-NET inferred observations were developed and examined in various applications, for example, a statistical evaluation Origin of pollution 1/3 of regional particulate matter concentrations are due to local emissions, while 2/3 originate from continental transport.…”
Section: Westbrook Andmentioning
confidence: 99%